Enhancing community health: Veterinary services for underserved areas in Costa Rica with a One Health Approach - Rojas-Sanchez, Ernesto (2024)
In underserved areas of Costa Rica, community veterinary services aim to provide comprehensive care for companion animals, covering preventive, therapeutic, and surgical medicine. Emphasizing a One Health approach, our model focuses on animal welfare, health, and public well-being in vulnerable regions. The project’s goal is to ensure the overall well-being of animals, people, and the environment by collaboratively addressing animal health issues and recognizing their interconnected impact on optimal health. Limited resources in underprivileged areas, including restricted access to veterinary care for pets, pose challenges to overall health. Despite its global health benefits, the absence of companion animal veterinary care in these regions has been largely overlooked. Our One Health approach not only addresses animal health but also has a significant impact on human and environmental health, economies, and social factors. This innovative strategy is a pioneering effort to tackle complex health issues in Costa Rica.